The process of creating algorithms for fundamental taekwondo training in the wtf style - Semenova G.I.; Erkomayshvili I.V.; Erkomayshvili I.V.; Ryabov G.A.; Pshenitsyn K.K. (Theory and Practice of Physical Culture, 2025)
Objective of the study was to determine the perspective of instructors regarding the implementation of algorithms in the teaching of fundamental techniques in Taekwondo. Methods and structure of the study. The research was carried out through a survey administered to taekwondo instructors. The survey consisted of both closed and open-ended questions designed to gauge the instructors' experience with the algorithmic approach, their perception of it, and their assessment of its effectiveness. A total of 22 instructors participated in the survey. Results and conclusions. A significant proportion of taekwondo instructors have been observed to employ the algorithmic approach, which suggests its potential effectiveness in teaching fundamental techniques and enhancing athletic performance. However, there are still challenges to implementing the algorithmic method in training, such as time constraints, a shortage of methodological resources, and a lack of motivation among athletes. These issues require further investigation to enhance the quality of athletes' training. This article will be of interest to coaches, instructors, and anyone seeking to improve their WTF taekwondo training methods.